SPATF - helping people to help themselves - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In ACP countries, as elsewhere, individuals and groups often want to improve their lives but lack the technology and skill to do so. The South Pacific Appropriate Technology Foundation (SPATF) is a community based, non-profit development...